Efektivitas Pembelajaran Kooperatif Tipe Jigsaw ditinjau dari Motivasi Siswa Terhadap Prestasi Belajar Matematika Siswa Kelas VIII MTS Abu Darrin Kendal Bojonegoro - nur rohman (LPPM Press, 2014)
This research aim is to know, 1) where give better influence, convensional learning orjigsaw toward learning acievement? 2) ) where give better influence in learning,studentwith high motivation,medium and low toward study acievement trig matery? 3) forstudent with various motivation, where learning model give batter influence, konvensionallearning or Jigsaw toward study trig acievement? Population in this research is all ofeighth Mts Abu Darrin Kendal, in the academic year of 2013/2014 is many as 109 studentsdivided become 4 class, with detail of class VIIIa consist from 28 students, VIIIb, VIIIcand VIIId this all class consist from 27 students. Be based on result cluster randomsampling, class become sample in the research is class VIIIa as experiment class andVIIIc as control class. Technique of analyzing the data in this research use variance twostreet analysis with difference sel. Prerequisite test involve the use of research analysisof data is normalitas test with Lilliefors methode and homogenitas test with Bartleetmethode. Conclusion: 1). Learning Mathematics Achievement of students teachableused Jigsaw Learning better than conventional learning, 2). Learning MathematicsAchievement of students with high motivation better then medium and low motivation.Such Learning Mathematics Achievement of students with medium motivation be betterthen low motivation. 3). There is not interaction between learning methode with studentsmotivation, so Learning Mathematics Achievement of students with high, medium andlow motivation teachable used Jigsaw Learning better than conventional learning.